2005
DOI: 10.1185/030079906x80341
|View full text |Cite
|
Sign up to set email alerts
|

Real-world utilization of DMARDs and biologics in rheumatoid arthritis: the RADIUS (Rheumatoid Arthritis Disease-Modifying Anti-Rheumatic Drug Intervention and Utilization Study) study

Abstract: These real-world data provide evidence of the prescribing practices of rheumatologists in 2001-2003. Future analyses will allow evidence-based comparisons of the long-term safety and effectiveness of DMARDs, biologics, and combination therapies to assist physicians in clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Data from the anti-rheumatic drug intervention and utilization study (RADIUS) study, a real-world prospective observational program of rheumatoid arthritis patients aimed at assessing prescribing patterns, safety and effectiveness of disease modifying anti-rheumatic drugs (DMARDs) and biologics, showed similar rates of biologic prescribing for the older (≥ 65 years) and younger (<65 years) patients. 31 Extrapolations from rheumatoid arthritis-based studies focusing on the older population indicate an increased risk of serious infection and hospitalization with immunosuppression, but the safety signals are greater with corticosteroids and non-biologic DMARDs compared to anti-TNF based therapies. 32, 33 …”
Section: Discussionmentioning
confidence: 99%
“…Data from the anti-rheumatic drug intervention and utilization study (RADIUS) study, a real-world prospective observational program of rheumatoid arthritis patients aimed at assessing prescribing patterns, safety and effectiveness of disease modifying anti-rheumatic drugs (DMARDs) and biologics, showed similar rates of biologic prescribing for the older (≥ 65 years) and younger (<65 years) patients. 31 Extrapolations from rheumatoid arthritis-based studies focusing on the older population indicate an increased risk of serious infection and hospitalization with immunosuppression, but the safety signals are greater with corticosteroids and non-biologic DMARDs compared to anti-TNF based therapies. 32, 33 …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that older age has little effect on differential DMARD selection for treatment of RA. [1,13,14,26] Based on these factors, we do not believe that dual use will substantially affect our estimates of impact of specific DMARDs on HFI risk.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world efficacy data were also reported from the Rheumatoid Arthritis DMARD Intervention and Utilization Study (RADIUS), a 5-year, multicenter, observational registry of patients treated with etanercept and other RA therapies in the United States ( N  = 10,061 in 2 cohorts) [26, 27]. Although safety data have not yet been reported, patients treated with etanercept, with ( p  < 0.01) or without ( p  < 0.05) methotrexate, were significantly more likely to have a modified ACR 20% response at 12 months compared with those receiving only methotrexate.…”
Section: Discussionmentioning
confidence: 99%